2004
DOI: 10.1029/2003ja010293
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dependence of localized, high‐latitude dayside aurora (HiLDA)

Abstract: [1] The FUV instrument on the IMAGE spacecraft frequently observes intense ultraviolet (UV) emissions from a localized High Latitude Dayside Aurora (HiLDA) poleward of the general auroral oval location [Frey et al., 2003a]. It has been shown that this aurora is entirely created by high-energy precipitating electrons, which have probably been accelerated in a quasi-static field-aligned electric potential. Here we extend the previous case study to an investigation of the HiLDA occurrence in the Northern Hemisphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(80 citation statements)
references
References 41 publications
11
69
0
Order By: Relevance
“…In the southern hemisphere we do not see any features that could ) which makes the northern lobe more exposed to the IMF than the southern lobe, and can explain why we see lobe reconnection in one hemisphere and not in the other. This is in agreement with Crooker and Rich (1993) who suggested that lobe reconnection is a summer phenomenon that can occur in one hemisphere only and Frey et al (2003bFrey et al ( , 2004 who found the HiLDA also to be a summer phenomenon.…”
Section: Convection Pattern In the Southern Hemispheresupporting
confidence: 81%
See 2 more Smart Citations
“…In the southern hemisphere we do not see any features that could ) which makes the northern lobe more exposed to the IMF than the southern lobe, and can explain why we see lobe reconnection in one hemisphere and not in the other. This is in agreement with Crooker and Rich (1993) who suggested that lobe reconnection is a summer phenomenon that can occur in one hemisphere only and Frey et al (2003bFrey et al ( , 2004 who found the HiLDA also to be a summer phenomenon.…”
Section: Convection Pattern In the Southern Hemispheresupporting
confidence: 81%
“…The combination of dayside reconnection and lobe reconnection was suggested by Reiff and Burch (1985) for weakly southward IMF with dominated B Y , which is exactly the IMF conditions we have. Compared to their Figure 1, our red line corresponds to their region L to M, and our green line (lobe reconnection) to their region between 10 M and H. The statistical studies by Frey et al (2003bFrey et al ( , 2004) also support our interpretation. In Figure 11C we have drawn (by hand) the same convection pattern and open-closed boundary onto the WIC color image from 17:47:00 UT.…”
Section: This Feature > 75supporting
confidence: 70%
See 1 more Smart Citation
“…The seasonal dependence of single auroral arcs appearing poleward of the main oval has been addressed by Frey et al [2004] for localized high‐latitude dayside aurora (HilDA) and by Cumnock [2005] for TPAs. Frey et al [2004] observed a maximum occurrence of HiLDAs during sunlit summer months and an almost complete absence in the dark winter. Cumnock [2005] found a similar seasonal dependence of the TPA luminosity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been observed that intense, localized, auroral emissions occur in the dayside polar cap during northward IMF (Milan et al, 2000;Sandholt et al, 2001;Fuselier et al, 2002;Frey et al, 2002Frey et al, , 2003Frey et al, , 2004Østgaard et al, 2005). Particle precipitation associated with the intense aurora could then cause significant ionization, resulting in regions of high electron concentrations that may lead to F region patches that can then convect across the polar cap.…”
Section: Introductionmentioning
confidence: 98%